2015
DOI: 10.1111/ajr.12143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sedentary behaviours among rural men working in offices and on farms

Abstract: In this study, farmers were less sedentary than rural men of similar age who work in offices. Further research is needed to identify reasons for the particularly high prevalence of chronic disease in Australian farmers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Although there is not a consensus regarding the daily cut-off values of sedentary time associated with increased mortality and disease incidence, a study published in 2018 with a meta-regression including more than one million participants suggests that nine hours per day or more of sedentary behaviour is associated with increased risk of mortality (hazard ratio = 1.22) in adults [39]. Our meta-analysis including two studies [32,35] that assessed sedentary time with accelerometers, found that the average sedentary time per day was 7.8 hours among the rural population. Similar results were found in a study that included data from 10 countries with populations from city-regions, which concluded that the average sedentary time per day, assessed through accelerometry, was 8.5 hours [40].…”
Section: Prevalence Of Sedentary Behaviour In Australian Adultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Although there is not a consensus regarding the daily cut-off values of sedentary time associated with increased mortality and disease incidence, a study published in 2018 with a meta-regression including more than one million participants suggests that nine hours per day or more of sedentary behaviour is associated with increased risk of mortality (hazard ratio = 1.22) in adults [39]. Our meta-analysis including two studies [32,35] that assessed sedentary time with accelerometers, found that the average sedentary time per day was 7.8 hours among the rural population. Similar results were found in a study that included data from 10 countries with populations from city-regions, which concluded that the average sedentary time per day, assessed through accelerometry, was 8.5 hours [40].…”
Section: Prevalence Of Sedentary Behaviour In Australian Adultsmentioning
confidence: 83%
“…The age range across the included studies was 18 to 93 years old, with seven studies including only women in their samples (Table 1). A total of 15 studies (54%) assessed physical activity subjectively with the Active Australia Survey or the long form of the International Physical Activity Questionnaire (IPAQ-L) [8,11,[13][14][15][16][17]19,21,23,[25][26][27][28][29], meanwhile only three studies (11%) reported measures using accelerometers [28,32,35]. Seven studies (25%) that assessed either physical activity or sedentary behaviour using a non-specified questionnaire or a questionnaire other than the Active Australia Survey or IPAQ were published up to 2010.…”
Section: Viewpoints Papersmentioning
confidence: 99%
“…Urbanization and technological advances in the workplace have been reported to be associated with a significant proportion of the decline in physical activities, particularly occupational physical activities [ 26 , 27 ]. Additionally, it has been suggested that mechanization in the agricultural sector may lead to increased sedentary behaviors among farmers [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…sedentary time) was calculated by summing up the duration of sitting/lying times within wake time epochs (also, the time of self-reported daytime naps were deducted, if exists). Participants with at least three valid weekdays of activPAL data (Pontt, Rowlands, & Dollman, 2015) and fulfilled GPAQ and SBQ, were included in the further analysis.…”
Section: Data Managementmentioning
confidence: 99%